Report of a Working Group on Allium (Fourth meeting): Held at Institut fur Genetik und Kulturpflanzenforschung, Gatersleben, Germany, 10 and 14 June 1991 - European Cooperative Programme for Plant Genetic Resources; International Board for Plant Genetic Resources (1991)
The 4th meeting of the Allium working group provides information on national collections, research activities and regeneration activites related to Allium genetic resources in Europe.